HIBAH ORANG TUA KEPADA ANAK SEBAGAI INSTRUMEN PENCEGAHAN SENGKETA WARIS PERSPEKTIF HUKUM ISLAM DI PONTIANAK KOTA - HAFIDZ AL GHIFARI; MUHAMMAD YASSIR (USRAH: Jurnal Hukum Keluarga Islam, 2026)
This study aims to analyze the normative provisions of hibah (inter vivos gift) in the Qur’an, Sunnah, and the Compilation of Islamic Law (KHI), to describe the practice of parental hibah to children in Pontianak Kota District, and to examine its conformity as an effort to prevent inheritance disputes. The research employs a qualitative approach with a socio-juridical method. Data were collected through in-depth interviews with five parents, five child recipients, and one notary, complemented by observation and document analysis. The findings indicate that hibah is normatively well-grounded in Islamic law and KHI, particularly regarding voluntariness, justice, and the protection of others’ rights. Empirically, community understanding of hibah is relatively adequate, yet its implementation remains limited and varies between informal and formal mechanisms. While most practices fulfill the essential pillars and conditions of hibah, deficiencies are found in transparency, fairness, and legal documentation. This study concludes that hibah can function as a preventive instrument against inheritance disputes, but its effectiveness is conditional upon consistent adherence to principles of justice, transparency, and legal certainty